THE SAFETY ISSUE OF ORTHOKERATOLOGY APPLICATION IN CLINICAL PRACTICE - Yu. S. Levchenko (Российский офтальмологический журнал, 2018)
In recent years, application of night orthokeratological contact lenses (OK lenses) is becoming more and more widespread the world over. Modern orthokeratology makes use of gas-permeable contact lenses of reverse geometry: these are sophisticated structures made from materials with high oxygen permeability. The change of the curvature of the external corneal surface and, as a result, ocular refraction changes caused by OK lenses occurs due to changing architectonics of the corneal epithelium. The safety of orthokeratology is a pressing issue. The percentage of revealed complications in patients wearing OK lenses is comparable to, and in some cases, is even lower than with other means of vision correction. If the choice of OK lenses is adequate and the patient wearing them complies with wearing instructions and maintenance rules, their long use does not entail clinically significant complications. The results of the study emphasize the importance of a careful choice of OK lenses and regular medical checkups of patients. For citation: Levchenko Yu.S. The safety issue of orthokeratology application in clinical practice. Russian ophthalmological journal. 2018; 11 (2): 87-94. doi: 10.21516/2072-0076-2018-11-2-87-94 (In Russian).